Moçambique - recessão antes do boom: Reflexões sobre picos de investimento e novas fontes de gás - Roe, Alan (2018)
Este artigo surge na sequência de um artigo anterior onde se considerou em termos gerais muitas das questões que Moçambique enfrenta hoje em dia na gestão dos seus novos recursos extractivos. Em primeiro lugar descreve-se o pico de investimento já desencadeado pelas novas descobertas de gás em Moçambique. Depois apresenta-se em resumo alguma da literatura mais recente sobre os efeitos desses picos noutros países e contextos. De seguida analisam-se os principais aspectos dos resultados económicos decepcionantes testemunhados até 2018, e analisase selectivamente algumas das implicações destes resultados nas políticas futuras. O artigo conclui explorando a epidemiologia de um grande pico do investimento público — uma questão que tem relevância para o pico adicional que ainda é esperado. Ao seguir esta sequência de argumento, procura-se igualmente compreender melhor diversas questões fundamentais de política geral que surgem no contexto das grandes descobertas de novos recursos.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Making Information Disclosure in Extractive Governance Count for Accountability in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (Partnership for African Social and Governance Research (PASGR), 2018)
A recent study on information disclosure in the extractive sector has found 18 factors that result in citizen and institutional (state and non-state) inaction in demanding government accountability. Conducted by the Partnership for African Social and Governance Research (PASGR) in collaboration with the Centre for Public Integrity (CIP), as part of the Action for Empowerment and Accountability (A4EA) research programme, the study shows that citizens and/or institutions are unlikely to demand government accountability when: • citizens’ are experiencing high levels of economic vulnerability but much of the access to economic opportunities are anchored around state patronage and network; • a single political party has dominated governments for a long period of time and the mode of selection of Parliamentarians is defined by a ‘party list’, and not directly elected by the people; • CSOs have weak citizens’ mobilisation strategies and information disclosure is presented in a written form in a context where adult illiteracy rate is 45%; • there is an institutional culture of ‘submissiveness’ created out of fear of the political regime
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; extractive industries / indústrias extractivas

What are the prospects for Mozambique to diversify its economy on the back of 'local content'? - Dietsche, Evelyn; Esteves, Ana Maria (WIDER Working Paper Series, 2018)
In recent years, Mozambique has made international headlines for the significant hydrocarbon deposits found offshore. These have increased the country's extractive resource endowments, in addition to its mining and onshore natural gas sector. It is expected that these industries will contribute to economic diversification and social development, not least by means of procuring locally produced goods and services and hiring Mozambicans. A key factor to achieve this is building domestic capital?in people, institutions, and infrastructure.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); ⛔ No DOI found

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

Minas a céu aberto de Moçambique - Munguambe, Arcénio Artur; Mandlate, Clarência Matias (Wutivi University, 2018)
Moçambique é um dos países da África com muitos recursos naturais. O grau de conhecime nto geológico até agora atingido, mostra que todos os recursos minerais considerados apresentam perspectivas favoráveis para a sua exploração. A indústria extrativa é o sector que tem grandes empregadores de mão-de-obra e tem um grande impacto rural podendo constituir grandes focos de desenvolvimento e de combate a pobreza nas áreas onde se encontra inserido. Neste caso, o presente trabalho visa identificar os principais recursos naturais e agrupar em metálicos e não metálicos e as respectivas empresas mineradoras.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Power, conflict and natural resources: The Mozambican crisis revisited - Macuane, José Jaime; Buur, Lars; Monjane, Celso Marcos (African Affairs, 2018)
This article explores how the present socio-economic crisis in Mozambique is linked to the prospects of natural resource windfalls for the country. Drawing on the political settlement approach, it explores how the distribution of power both within and outside the ruling elite is structured and consequently how the underlying political processes have been shaped by the expectations of natural resource windfalls. The article argues that the present socio-economic crisis in Mozambique is not due to national resource assets in themselves. Instead, the political and economic downturn in Mozambique should be understood as a manifestation of how the political settlement has been organized and rent mobilization controlled by the ruling elite. To understand how the prospect of rents from natural resource sectors have influenced the political settlement, we have argued that one has to look at the dynamics of power both within and outside the ruling elite and the incentives they create for elites to use the control of power and access to economic benefits to achieve narrow and short-term gains rather than inclusive and longer-term goals.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; extractive industries / indústrias extractivas; natural resources / recursos naturais; power / poder

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Extractives and economic diversification in Mozambique: will local content do the trick? (Research Brief 2/2018, 2018)
Research Findings - It is unlikely that the extractives sector can any time soon be used to finance visionary transformation strategies aimed at achieving economic diversification. Due to the country’s fiscal situation and delays in developing the offshore natural gas sector, it seems that extractives will not provide additional revenues for at least another decade, if not longer. If the fiscal crisis results in the further deterioration of the provision of public goods and services, the business environment will become worse for the country’s micro, small and medium-sized enterprises. There is the risk that the gap will widen even further between the skills and entrepreneurial capabilities available in the country, and those required by foreign investment projects and their supply chains. Such a prospect does not match well with the expectations that local content policies can provide the silver bullet for diversifying the economy.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector / setor privado